Análisis crítico del régimen de transparencia fiscal internacional vigente en el perú a partir del 2013 - Villagra Cayamana, Renée Antonieta (2013)
In the current globalization state, emerges an important problem referred to tax deferral, committed by those who, taking advantage of their belonging to entities domiciled abroad, are able to avoid paying taxes for what the yearn. In these cases, the governments are theo nes impaired, because they do not perceive the incomes they should. This is the reason why a Fiscal Transparency Regime is proposed, so that those incomes can be assessed. In this article, the author analyses the recent incorporation of that transparency regime to Peruvian legislation and accomplishes to build a scheme that, while comparing national legislation with other regimes abroad, permits to explain its main characteristics, as well as its benefits and deficiencies.